Analisis Pemanfaatan Aplikasi iPusnas sebagai Sumber Belajar oleh Mahasiswa Ilmu Perpustakaan dan Informasi Islam IAIN Curup - Rizkyantha, Okky; Yumiarti, Yuyun; Cahaya, Ory (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to determine the use of the iPusnas application as a learning resource by IAIN Curup Islamic Library and Information Science students and to determine the inhibiting factors in the use of the iPusnas Application as a Learning Resource by IAIN Curup Islamic Library and Information Science Students. This study used a type of descriptive qualitative research using interview, observation, and documentationtechniques. The informants in this study are two students of Islamic Library and Information Science class of 2020, two students of IslamicLibrary and Information Science class of 2021, and two students of Islamic Library and Information Science class of 2023. From the results of the research, researchers can find that the use of the iPusnas application as a learning resource by students of Islamic Library and Information Science when viewed from the aspect of usefulness and ease in learning activities is still not optimal. Because references to books, journals, and articles are still limited and there is still a lack of user understanding in using existing features to find learning references. So users can't find the books, journals, and articles they want. But even so, users feel that it has been helped by utilizing the iPusnas application, users can find other books as their learning references. The inhibiting factors in the use of the IPUSNAS application as a learning resource are divided into internal factors and external factors. The internal factor is that this application still has many errors or system errors. The collection available on the iPusnas application is still small. And the external factor, namely the user's regular internet connection that is unstable or slow, is an inhibiting factor in the use of the iPurnas application.